Calibration and Performance Evaluation of Radar QPE and QPF in Klang River Basin - Hasni, Hannani; Tahir, Wardah; Osman, Noor Shazwani; Haron, Nuryazmeen Farhan (International Journal of Sustainable Construction Engineering and Technology, 2024)
Accurate hydrological data is crucial for the use of sustainable environmental monitoring and disaster management purposes. The flood that occurred in December 2021 in the Klang River Basin serves as a valuable lesson on the significance of accurate rainfall forecasts to anticipate any undesirable catastrophe from taking place. The usage of weather radar to forecast quantitative rainfall has been challenging especially now that the climate is experiencing unpredictable changes. In this study radar quantitative precipitation estimates (QPE) and quantitative precipitation forecast (QPF) in Klang River Basin have been calibrated using the mean field bias (MFB) and mean assessment factor (MAF) correction techniques. The performance analysis compares the radar QPE and QPF with mean areal gauge rainfall using Thiessen Polygon Method and point gauges of 21 rainfall stations located in the basin. Results show that the MFB correction technique performs better than the MAF technique with higher correlation coefficient and less error. Radar QPF performance assessment indicates improved accuracy in calibrated values especially for shorter lead time, but the correctness is inconsistent.